ECOBIOLOGICAL PROPERTIES OF SUNFLOWER (HELIANTHUS ANNUUS L.): GROWTH DYNAMICS, ENVIRONMENTAL INTERACTIONS, AND AGRICULTURAL SIGNIFICANCE - Rahimova Gulnoza Yomgirovna (Innovate Conferences, 2025)
Sunflower (Helianthus annuus L.) is an annual plant belonging to the Asteraceae family and is one of the primary oilseed crops. Its origin is North America. The wild sunflower was brought to Europe by the Spanish in 1510. Initially, it was cultivated as an ornamental plant. The plant has a well-developed taproot, an erect and rough stem that branches at the upper part and can reach up to 4 meters in height. The leaves are simple, large, alternately arranged, and covered with coarse hairs. The inflorescence is a capitulum (head) with a diameter of 35–40 cm. The central flowers of the head are tubular and bisexual, while the peripheral flowers are reddish-yellow and ligulate. Sunflower undergoes cross-pollination. The fruit is an achene, four-sided, and varies in colour from white to grey and black.